197k views
9 votes
{2x
x = -6y
12x + 12y = 0
Solve the system of equations.

User AleMal
by
5.3k points

1 Answer

13 votes

Answer:

The solution to the system of equations is:


x=0,\:y=0

Explanation:

Given the system of equations

2x = -6y

12x + 12y = 0

solving the system of equations by elimination method


\begin{bmatrix}2x=-6y\\ 12x+12y=0\end{bmatrix}

Arrange equation variables for elimination


\begin{bmatrix}2x+6y=0\\ 12x+12y=0\end{bmatrix}

Multiply 2x+6y = 0 by 6: 12x+36y=0


\begin{bmatrix}12x+36y=0\\ 12x+12y=0\end{bmatrix}

subtracting the equations


12x+12y=0


-


\underline{12x+36y=0}


-24y=0

solve -24y=0 for y


-24y=0

divide both sides by -24


(-24y)/(-24)=(0)/(-24)

Simplify


y=0

For 12x+36y=0 plug in y = 0


12x+36y=0


12x+36\cdot \:0=0


12x+0=0


12x=0

Divide both sides by 12


(12x)/(12)=(0)/(12)

Simplify


x=0

Therefore, the solution to the system of equations is:


x=0,\:y=0

User Momoja
by
6.4k points